Potential of Organic Complexing Agents in Enhancing Fenton and Photo-Fenton Reactions: A Sustainable Approach Using Solar Irradiation for Emerging Contaminants Treatment - Oliveira Silva, Marciele; Bernardes Marques, Maiara; de Souza, Danilo Rodrigues (Orbital: The Electronic Journal of Chemistry, 2025)
This study investigates the influence of organic complexing agents on the Fenton and photo-Fenton reactions to degrade diclofenac sodium (SDF). The effects of adding sodium citrate and sodium oxalate were investigated. A factorial experimental design evaluates pH, irradiation source, and the citrate:Fe2+ ratio. Solar photodegradation and acute toxicity tests were conducted to evaluate process performance. HPLC-UV and TOC techniques were monitored diclofenac sodium concentrations, while bioassays with Artemia salina assessed toxicity reduction. The results showed that organic complexing agents, particularly sodium citrate, significantly improved photocatalytic efficiency. The experimental design validated the feasibility of using LED lamps for irradiation, demonstrating excellent performance at neutral pH when higher concentrations of sodium citrate were employed. Solar photocatalytic tests showed photodegradation rates exceeding 90%, while TOC and toxicity reduction analyses revealed approximately 80% and 100% efficiencies, respectively. These findings contribute to environmental science by presenting an efficient, sustainable, and adaptable technology for emerging contaminant degradation. .